Dibujando la nación desdibujando al enemigo: Imágenes de movilización bélica en la prensa de guerra paraguaya, 1867-1868 - Johansson, Maria Lucrecia (2016)
Between 1864 and 1870, the Paraguayan forces clashed with the armies of Argentina, Brazil and Uruguay, in what was called the War of the Triple Alliance (1864-1870). During that war, the Paraguayan government revolutionized journalism by the creation of two illustrated newspapers: El Centinela and Cabichuí (1867-1868). The engravings of these newspapers created a system of opposition we/they that rested on opposite values and in the opposition between negative and positive images. The aim of this paper is to analyse how the press built negative images of the enemy and how those images were the basis for creating a positive representation of Paraguay.